Cannabis sativa L. roots extract modulates gastrointestinal motility and ameliorates ethanol-induced gastric ulcers in animal models - Sá, Pedro Guilherme Sousa de; Rocha, João Gabriel de Souza; Silva, Juliane Maria dos Santos; Souza, Nathália Andrezza Carvalho de; Araújo, Tarcísio Cícero de Lima; Santos, Victória Laysna dos Anjos; Menezes, Pedro Modesto Nascimento; Palheta Junior, Raimundo Campos; Silva, Fabrício Souza; Rolim, Larissa Araújo (Frontiers in Pharmacology, 2026)
IntroductionCannabis sativa L. roots are traditionally used to manage gastrointestinal (GI) disorders; however, experimental pharmacological evidence supporting these uses remains limited. This study investigated the chemical profile, safety, and GI-related pharmacological effects of an ethanolic extract of C. sativa roots (CEECs).MethodsChemical characterization was performed by spectrophotometric determination of total triterpenes and HPLC profiling. Safety and pharmacological effects were assessed through acute oral toxicity testing, antibacterial assays, and in vivo murine models of gastric emptying, diarrhea, and ethanol-induced gastric ulcer.ResultsCEECs showed a total triterpene content of 67.64 ± 5.39 μg LE·mg−1, and HPLC analysis detected p-coumaric acid and N-trans-feruloyltyramine. In vivo, CEECs significantly delayed gastric emptying at 50 mg·kg−1 (P = 0.0033) and reduced fecal output in the castor oil-induced diarrhea model at 50 (P < 0.001) and 100 mg·kg−1 (P = 0.0233), with no effect in the magnesium sulfate-induced model. CEECs also significantly reduced ethanol-induced gastric mucosal injury at 50 mg·kg−1 (P = 0.0484) and 100 mg·kg−1 (P = 0.0164). No signs of acute toxicity were observed at 2000 mg·kg−1. Antibacterial activity against Staphylococcus aureus strains was weak under the tested conditions.DiscussionThese findings provide experimental support for the traditional use of C. sativa roots in GI disorders and indicate their potential as a non-psychoactive source of bioactive constituents.